Global burden and genetic insights of RA and JIA in ages 0–19 years: GBD 2021 and MR analysis - An, Pingyu; Ma, Zhiqiang; Tian, Tian; Zhang, Shibo; Wang, Jian; Tian, Zhiliang (Frontiers in Immunology, 2026)
BackgroundRheumatoid arthritis (RA) is a chronic autoimmune arthritis that predominantly affects adults, whereas juvenile idiopathic arthritis (JIA) comprises a heterogeneous group of childhood−onset arthritides defined by age at onset, clinical phenotype, and immunological profile. Although RA and JIA are classified as distinct diseases, they share overlapping clinical and immunological features, and the nosological relationship between RA and some JIA subtypes remains debated. The global burden of RA and JIA in young people, and the similarities and differences in their underlying immunogenetic features, remain incompletely understood.MethodsWe utilized GBD 2021 data to describe trends in incidence, prevalence, and disability-adjusted life years for RA in individuals aged 0–19 years, as defined within the GBD framework, from 1990 to 2021. In parallel, we performed two−sample Mendelian randomization (MR) using genome−wide association study summary statistics from European−ancestry cohorts to assess associations of genetically proxied levels of 731 immune−cell traits, 91 circulating inflammatory proteins, and 1,400 serum metabolites with RA and JIA risk.ResultsFrom 1990 to 2021, global age−standardized incidence and prevalence of RA in individuals aged 0–19 years increased, whereas disability−adjusted life years declined slightly. The aggregated burden was higher in females and in high−sociodemographic index regions. MR identified overlapping genetically proxied immune−cell and inflammatory protein traits for RA and JIA, including CD28 on CD8+CD45RA+ T cells, CD25 on memory B cells, signaling lymphocytic activation molecule, and Fms−like tyrosine kinase 3 ligand, whereas higher genetically predicted levels of activated regulatory T cells and HLA−DR on dendritic cells were associated with lower risk in both diseases.ConclusionOur study highlights a rising global burden of GBD−defined RA among children and adolescents and delineates shared and distinct patterns of genetically predicted immune−cell, inflammatory protein, and metabolite traits associated with RA and JIA. These observations suggest that immunologically informed approaches could complement existing age- and phenotype-based classifications and help refine early recognition and risk stratification of inflammatory arthritis across the life course.